Effects of nanoparticles on photopolymerization of acrylate monomers in forming nano-composites. (September 2015) - Check, Casey; Chartoff, Richard; Chang, Sean
Graphical abstract: Highlights: Optically transparent nano-composites containing ZrO2 nanoparticles were formed by UV photopolymerization. Nanoparticles significantly increased the degree of polymerization conversion achieved for a given UV light exposure. The reaction kinetics differ for different specific monomer–nanoparticle systems. The differences in kinetics must be taken into account in forming the composites. Abstract: The UV photopolymerization of diethylene glycol-diacrylate and isobornyl-acrylate based nano-composites was studied with respect to reaction conversion with variations in UV light exposure. The composites contained various amounts of well dispersed ZrO2 nanoparticles. The degree of conversion achieved vs light intensity was measured by DSC for various compositions ranging from 0 to 30% by weight of nanoparticles. It was found that including nanoparticles in the monomer increased the conversion achieved considerably. This is attributed to the acceleration of the reaction through interactions with the silane surface ligand on the nanoparticles. The upper limit for conversion was limited because of vitrification and was different for each monomer. Also noted was that the detailed effects of particle concentration on conversion are quite different for the two monomers. Conversion vs UV exposure data such as those presented provide information necessary for determining the appropriate UV exposure required for creating nano-composites by inkjet printing with optimized physical, mechanical, and optical properties. The results indicate that it is important to determine this information for forming nano-composites from any specific monomer/nanoparticle combination.